Pengaruh Kualitas Layanan AKJP II Pekanbaru Terhadap Kepuasan Mahasiswa Dengan Metode IPA Dan CSI - Anna Maria (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2021)
This study aimed to analyze level of interest and performance with Importance Performance Analysis (IPA) and Customer Satisfaction with Customer Satisfaction Index (CSI). The results of 40 attributes (tangibles, reliability, responsiveness, assurance, emphaty) were described in cartesian plane scattered in 4 quadrants. Quadrant I illustrated high interest, low performance, being top priority. Quadrant II showed high interest and performance requiring sustainable achievement. Quadrant III highlighted low interest and performance paid less attention. Quadrant IV summarized low interest yet high performance, emphasizing re-allocation of resources. Efforts to improve quadrant I: MoU for learning experience and with other libraries, tutorial video, procurement of instruments, sorting and planning of collection including e-book, provision cleaning tools and furniture in public spaces, facility maintenance, recruitment of laboratory assistants and professionals, extending boundary wall, installing more cctv camera, optimalization of e-services, socialization of SOP. Level of student satisfaction with CSI index obtained 97.10% (highly satisfied). Key Words: Service Quality, Customer Satisfaction, Importance Performance Analysis, Cartesian Plane, Customer Satisfaction Index.